2020
DOI: 10.5606/ehc.2020.71334
|View full text |Cite
|
Sign up to set email alerts
|

Can infection after anterior cruciate ligament surgery be prevented by inserting a Hemovac drain into graft donor site?

Abstract: Anterior cruciate ligament (ACL) reconstruction surgery is a highly successful orthopedic surgery providing both functional stability of the knee and more active participation of a person in daily life. [1,2] Postoperative infection following ACL reconstruction in normal population is reported to be highly rare with the incidence rate of only 0.14 to 1.4%. [2-8] On the other hand, the incidence rate among professional athletes was reported as high as 5.7%. [9] Although the occurrence of postoperative infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“… 19 Another study suggested that through reducing hematoma occurrence postsurgery using a Hemovac drain, deep surgical site infections could be reduced when using hamstring tendon allografts. 20 Given the results of our study, it is important to consider the role of ACL infection prevention given the favorable outcomes presented in several studies performed.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“… 19 Another study suggested that through reducing hematoma occurrence postsurgery using a Hemovac drain, deep surgical site infections could be reduced when using hamstring tendon allografts. 20 Given the results of our study, it is important to consider the role of ACL infection prevention given the favorable outcomes presented in several studies performed.…”
Section: Discussionmentioning
confidence: 93%
“…Some studies, including a systematic review by Xiao et al, found that soaking ACL tendon grafts with vancomycin before implantation was associated with a nearly 15 times decrease in infection compared with grafts not soaked 19 . Another study suggested that through reducing hematoma occurrence postsurgery using a Hemovac drain, deep surgical site infections could be reduced when using hamstring tendon allografts 20 . Given the results of our study, it is important to consider the role of ACL infection prevention given the favorable outcomes presented in several studies performed.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior cruciate ligament (ACL) is one of the primary ligaments of the tibio-femoral joint and has an important role in the motion and stabilization of the knee [1][2][3][4][5][6][7][8]. ACL injuries are one of the important health problems affecting the quality of life of individuals, and many reasons can lie in the etiology from injuries to wrong movements in sports activities.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative hematoma is a suitable environment for the growth of bacteria and increases the risk of postoperative infection [5]. Drainage of the hematoma in a surgical wound is considered effective in reducing infection [6].…”
Section: Introductionmentioning
confidence: 99%